Correlation between Na 2SiO 3/NaOH ratio and fly ash/alkaline activator ratio to the strength of geopolymer - Mohd Mustafa Al Bakri, Abdullah (Trans Tech Publications, 2013)
Link to publisher's homepage at http://www.ttp.net/